Work done in the margins: A comparative study of mental health literacy in pre‐service teacher education in Australia and in Scotland. Issue 4 (4th March 2019) - Armstrong, David; Macleod, Gale; Brough, Colin
Abstract : Ensuring pre‐service teachers have strong mental health literacy is vital for progress towards an inclusive, effective education system; yet little is known about how pre‐service teachers are prepared for practice with school students who present with poor mental health. The original, internationally comparative small‐scale (N = 24) qualitative study reported here compared current mental health literacy provision to pre‐service teacher education students in Scotland and Australia. Semi‐structured telephone interviews with teacher educators who delivered mental health content divulged highly variable, often ad‐hoc mental health literacy provision; a concern, given the prevalence of poor mental health affecting children and young people in schools. Thematic data analysis revealed striking commonalities among issues raised by participants from both countries, highlighting the need for urgent improvement in the provision of mental health literacy to pre‐service teachers. Results suggest the possibility of strategically developing a joint Australian‐Scottish mental health component suitable for delivery in both countries.